Targeting prolific and other priority offenders and promoting pathways to desistance: Some reflections on the PPO programme using a theory of change framework. (November 2013) - Hopkins, Matt; Wickson, Julia
The Prolific and Other Priority Offender (PPO) programme was introduced in 2004 to target the most prolific and persistent offenders within Community Safety Partnership areas. Based on identifying offenders through local crime analysis, intensive supervision and targeted intervention, evaluations have shown promising results. By using a 'theory of change' approach as an analytical framework and a local PPO project as a case study, this article begins to question whether the rationale behind the PPO programme can be viewed as 'plausible', if key strands of implementation are 'doable' and if the desired outcomes are 'testable'. The article argues that although the rationale for the PPO programme might be plausible, doubts are raised over its likely impact on local crime rates and the extent PPO projects might be able to target prolific offenders effectively. Finally, it suggests that although testable outcomes can be established, the extent to which the programme has enhanced our understanding of desistance is questionable.